El Efecto Devolutivo de la Apelación a Sentencias Condenatorias Privativas de Libertad por Contravenciones Flagrantes y los Derechos Constitucionales del Debido Proceso y Presunción de Inocencia” - Pacheco Correa, Genner Stalin (2018)
Since the Montecristi Constitution 2008, our country Ecuador is a constitutional state of rights and social justice. That is, its legal system has been designed in order to guarantee the rights of persons in general, whether they are victims or accused. Our legislators have designed legal tools based on the constitution and in relation to international instruments that have been analyzed in this work in order to have a deeper knowledge and be able to make an analysis based on what our Constitution and international instruments have. This research work study especially the right to appeal, to appeal or to double compliance and how to execute it in order to avoid violating this and other rights related to it. Analyzing theoretical and legal bases, I have been able to define in a more specific way the right to have recourse, to appeal or to double-check, as a constitutional guarantee. Therefore, the study of our Constitution, of constitutionalist experts, and of the international treaties in force has been indispensable. From the analysis of some writers and the knowledge acquired during the investigation, we can conclude that the right to recourse, to appeal or to double compliance is a universal right. It comes from the Roman era, which in addition, in our legislation and in some other parts of the world is part of due process, that is, it is a procedural part in which the person being 5 prosecuted can pronounce his non-conformity with the sentence. This act is known as a challenge, and after expressing and sustaining this disagreement, the judge gives way to a higher judge who will be in charge of reviewing the process again and making the necessary observations on the rights of the accused. After, the higher judge will pronounce himself or herself with a ratifying, modifying or acquitting sentence. This stage of challenge in our legal system is extremely important for the application of double standards because it is here where the bases that support the vulnerable subject in the criminal process must be built. The contribution of this work is that the justice Ecuadorian administrators should be able to apply this guarantee correctly to the double extent that although it is true that our legislation recognizes it but it is being misapplied. As well, there should be a regulation for the effects of appeal in the case of flagrant infringements, and that in this way there should be no attempt to evade justice by applying a suspensive effect in the appeal of flagrant infringements.